The effect of awarding and work environment on employee job satisfaction of PT Angkasa Pura II Halim Perdana Kusuma Airport - Syahairony, M.; Zulham, T.; Patiro, Pintor Siolemba (SEAN Institute, 2024)
The purpose of this research is to determine and explain the influence of giving awards on employee job satisfaction and to examine the influence of the work environment on employee job satisfaction at PT Angkasa Pura II Halim Perdana Kusuma Airport. The sample in this research was employees of PT Angkasa Pura II Halim Perdana Kusuma Airport in 2022, totaling 42 people. The data collection method used in this research is a questionnaire. This type of research uses quantitative methods, using descriptive and inferential data analysis techniques with determinant coefficient analysis. The data in this study were analyzed using multiple regression analysis. The findings in this research are that giving awards and the work environment have a significant and positive effect on the job satisfaction of PT Angkasa Pura employees, both partially and simultaneously.